Increased IL-23R+ Th Cells Population Exhibits Higher SLEDAI-2K Scores in Systemic Lupus Erythematosus Patients - Aziz Farah Izati; Aziz Farah Izati; Nur Diyana Mohd Shukri; Nur Diyana Mohd Shukri; Wan Syamimee Wan Ghazali; Wan Syamimee Wan Ghazali; Che Maraina Che Hussin; Che Maraina Che Hussin; Kah Keng Wong; Kah Keng Wong (Frontiers in Immunology, 2021)
The IL-23/IL-17 axis plays causative roles in the development and progression of systemic lupus erythematosus (SLE). However, it remains unclear if the IL-17RA+ and IL-23R+ T helper (Th) cells populations are associated with the serum IL-17 and IL-23 levels, or with the immunological parameters and disease activities in SLE patients. Herein, we examined the proportion of IL-17RA+ and IL-23R+ Th cells and serum levels of IL-17 and IL-23 in established SLE patients (n = 50) compared with healthy controls (n = 50). The associations of these interleukins and their receptors with immunological parameters [anti-nuclear antibody (ANA), anti-dsDNA antibody, and C-reactive protein (CRP)] and SLE disease activity (SLEDAI-2K scores) in SLE patients were assessed. CD3+CD4+ Th cells of SLE patients demonstrated significantly elevated IL-17RA+ (p = 1.12 x 10-4) or IL-23R+ (p = 1.98 x 10-29) populations compared with the healthy controls. Serum IL-17 levels were significantly lower in SLE patients compared with the healthy controls (p = 8.32 x 10-5), while no significant difference was observed for the IL-23 serum levels between both groups. IL-23R+ Th cells population was significantly associated with higher SLEDAI-2K scores (p = 0.017). In multivariate analysis, the proportion of IL-23R+ Th cells remained significantly associated with higher SLEDAI-2K scores independent of prednisolone intake (p = 0.027). No associations were observed between the interleukin parameters (i.e., IL-17, IL-23, IL-17RA+ Th cells, and IL-23R+ Th cells) with ANA, anti-dsDNA, and CRP status, suggesting that the IL-17/IL-23 axis acts independently of these immunological parameters. In conclusion, our results support that therapeutic inhibition of the IL-23/IL-17 axis receptors on Th cells, particularly IL-23R, is potentially relevant in SLE patients.